Novel fluorescent sensors for dynamic intracellular signalling - Schleifenbaum, Andreas (2005)
Protein kinase C (PKC), comprised of ten isozymes, is an abundant regulator of cellular function. PKC activity in living cells is commonly assayed in in vitro experiments with cell lysate. Monitoring PKC activity in single living cells is not possible with such experiments. This thesis presents a novel fluorescent reporter for PKC activity in living cells. The kinase C probe (KCP-1) consists of a PKC specific substrate sequence that is flanked by two fluorescent proteins, which are capable of fluorescence resonance energy transfer (FRET). The substrate sequence is truncated pleckstrin, which is specifically phoshorylated by PKC between a pleckstrin homology and DEP domain. Green fluorescent protein square (GFP2) and enhanced yellow fluorescent protein (EYFP) were chosen as FRET partners, because of their perfect overlap of donor emission and acceptor excitation. The probe reported PKC activity after stimulation of cells with drugs and mitogens, including phorbol ester, diacylglycerol, histamine, and bradykinin. The KCP-1 signal was reversed after cell treatment with the PKC specific inhibitor Gö6983. Stable cell lines and transgenic fly embryos which expressed KCP-1 demonstrated that the probe was not toxic to cells. Live cell or in vitro tests demonstrated KCP-1 specificity for PKC over protein kinase A (PKA), calcium/calmodulin dependent kinase (CaMKII), protein kinase B, and aurora kinases. These experiments demonstrated that KCP-1 can be used in living cells to specifically monitor PKC activity. KCP-1 was simultaneously observed in single cells with other fluorescent probes, including indicators for the PKC activators calcium and diacylglycerol. These tests demonstrated feasibility and limitations of such experiments. Furthermore, these, as well as in vitro experiments suggested that KCP-1 primarily reported activities of calcium independent PKC isozymes. One application of KCP-1 is drug-screening assays. Initial experiments with the stable cell line demonstrated that the probe can be used in such assays after further optimization of experimental parameters. Optimization of the probe involved modification of several features: KCP-1 mutants were altered in the membrane targeting PH domain. These constructs lacked residual translocation activity of this domain. The probes PKC substrate loop harboured three phosphate acceptor amino acids. These were mutated systematically to alanines or glutamates. Comparison of responses from the different mutants showed a) that one specific serine in KCP-1 was necessary and sufficient to produce a maximal response and b) that these three amino acids contributed differently to the FRET change. Potentially, these results can be conferred to pleckstrin, a protein of unknown function. Furthermore, KCP-1s substrate loop was altered to extend specificity to other kinases. One of the engineered constructs responded to PKA activation. In summary, a novel FRET reporter for PKC activity was developed and its applications and limitations were tested. The probes specificity could be extended to PKA and therefore, the reporter may serve as a platform for further probe development.